Antifungal Activity of Selected Naphthoquinones and Their Synergistic Combination with Amphotericin B Against Cryptococcus neoformans H99 - Naira Sulany Oliveira de Sousa; Juan Diego Ribeiro de Almeida; Linnek Silva da Rocha; Izabela de Mesquita Bárcia Moreira; Flávia da Silva Fernandes; Ani Beatriz Jackisch Matsuura; Kátia Santana Cruz; Emersom Silva Lima; Érica Simplício de Souza; Hagen Frickmann; João Vicente Braga de Souza (Antibiotics)
Background/Objectives: Cryptococcosis, caused by Cryptococcus neoformans and Cryptococcus gattii species complexes, remains a significant health concern, particularly among immunocompromised patients. The emergence of antifungal resistance and toxicity of conventional treatment underscore the urgent need for novel therapeutic approaches. Combination therapies represent a promising strategy to enhance efficacy and overcome resistance. This study investigated the antifungal activity of five naphthoquinones against nine isolates of Cryptococcus spp. and assessed their synergistic effects with amphotericin B (AmB). Methods: In this study, five selected naphthoquinones were evaluated for their antifungal activity against Cryptococcus spp. isolates using broth microdilution assays to determine minimum inhibitory concentrations (MICs), according to CLSI guidelines. The potential synergistic effect with AmB was assessed using checkerboard assays, with synergy interpreted based on the fractional inhibitory concentration index (FICI). Cytotoxicity was evaluated in MRC-5 human lung fibroblast cells using the MTT assay. Results: Among the compounds tested, 2-methoxynaphthalene-1,4-dione (2-MNQ) demonstrated antifungal activity, with MIC values ranging from 3.12 to 12.5 µg/mL. Checkerboard assays revealed a synergistic interaction between 2-MNQ and AmB, with a fractional inhibitory concentration index (FICI) of 0.27. The combination reduced the MIC of AmB by 4.17-fold. These findings highlight the potential of synthetic naphthoquinones, particularly 2-MNQ, as effective antifungal agents with synergistic properties when combined with AmB. The observed synergy suggests complementary mechanisms, including increased fungal membrane permeability and oxidative stress induction. Conclusions: This study highlights the potential of 2-MNQ and 2,3-DBNQ as antifungal candidates against Cryptococcus spp., with emphasis on the synergistic interaction observed between 2-MNQ and amphotericin B. The findings reinforce the importance of structural modifications in naphthoquinones to enhance antifungal activity and support the need for further preclinical studies investigating combination therapies aimed at improving treatment efficacy in patients with cryptococcosis.